Factors affecting toxic lead(II) ion bioremediation by Fusarium equiseti isolated from the mangrove soil environment of southeast Borneo - Wahab Abideen, Akinkunmi; Awang Ahmad Sallehin, Awang Husaini; Azham, Zulkharnain; Tay, Meng Guan; Hairul, Azman Roslan (Malaysian Society of Microbiology, 2015)
Electronic waste (e-waste) is an inorganic pollutant which causes a serious environmental problem since it contains toxic heavy metals, which cannot be removed from contaminated sites easily. The use of biomaterials for removing heavy metals from contaminated soil and wastewater has emerged as a potential alternative method to the conventional techniques. The present study were aimed to isolate efficient lead tolerant fungi from mangrove soil environment and measure its capability for lead removal from aqueous solution.Lead tolerant fungal strains were isolated from soil samples using PDA (Potato Dextrose Agar) supplemented with varied concentrations of lead ions (100-500 mg/L). The most tolerant fungal strain was successfully isolated and identified molecularly as Fusarium equiseti KR706303. The isolated fungus was used for biosorption studies using Potato dextrose broth (PDB) supplemented with lead ions. The effects of pH, temperature, initial metal concentration, biomass dose and age, agitation and contact time to the Pb(II) removal efficiency were monitored in the study. The results showed that the optimal parameters for the removal of lead ions such as heavy metal concentration and pH were 300 mg/L, with a maximum Pb(II) adsorption of 97.9% observed at pH 4 and temperature of 30 °C during the batch biosorption experiments. The optimal parameters for biomass dose, agitation speed, contact time and biomass age were observed at 0.04 g, 150 rpm, 60 min and fifth day; respectively.The observation in this study revealed that the biomass of the isolated Fusarium equiseti KR706303 has the potential to be used as a biosorbent for heavy metal particularly Pb(II) removal from the contaminated sites. The technology is simple, efficient, cost effective and environmental friendly.